2010
DOI: 10.1007/s00232-010-9314-x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Macromolecule Complex with Bacillus thuringiensis Cry1A Toxins and Chlorophyllide Binding 252-kDa Lipocalin-Like Protein Locating on Bombyx mori Midgut Membrane

Abstract: P252, a 252-kDa Bombyx mori protein located on the larval midgut membrane, has been shown to bind strongly with Bacillus thuringiensis Cry1A toxins (Hossain et al. Appl Environ Microbiol 70:4604-4612, 2004). P252 was also shown to bind chlorophyllide (Chlide) to form red fluorescence-emitting complex Bm252RFP with significant antimicrobial activity (Pandian et al. Appl Environ Microbiol 74:1324-1331, 2008). In this article, we show that Cry1A toxin bound with Bm252RFP and Bm252RFP-Cry1A macrocomplex, with both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Arylphorin functions in the storage of the aromatic amino acids but it also plays a central role in insect immunity. 20 Spot 5 showed homology to lipocalin, which functions in the immune response by binding to toxins and by complexing invading pathogens 21 and its expression was reduced by approximately 14% in starved larvae. Ferritin (spot 1) and transferrin precursor (spot 6) were reduced in expression by approximately 50% in food-deprived larvae.…”
Section: Resultsmentioning
confidence: 99%
“…Arylphorin functions in the storage of the aromatic amino acids but it also plays a central role in insect immunity. 20 Spot 5 showed homology to lipocalin, which functions in the immune response by binding to toxins and by complexing invading pathogens 21 and its expression was reduced by approximately 14% in starved larvae. Ferritin (spot 1) and transferrin precursor (spot 6) were reduced in expression by approximately 50% in food-deprived larvae.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was shown that polycalin is not likely to be involved in toxicity in B. mori (Pandian et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Polycalin was reported to bind to Cry toxin in B. mori (Hossain et al 2004;Pandian et al 2008) and H. armigera (Angelucci et al 2008;Ma et al 2012). However, it was shown that polycalin is not likely to be involved in toxicity in B. mori (Pandian et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Later, it was found that the polycalin in H. armigera could bind with Cry1A and Cry2A toxins according to liquid chromatograghy–mass spectrometry (LC–MS)/MS, MS data, and binding results (Angelucci et al, 2008; Wang et al, 2019; Zhou et al, 2016). Importantly, some findings showed the macrocomplex of chlorophyllide (Chlide), polycalin and Cry1Ab can reduce the insecticidal activity when comparing with Cry1Ab alone (Pandian et al, 2010). In H. armigera , polycalin not only binds to Cry2Aa, but is also involve in the toxicity of Cry2Aa (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%